Potret Kaum Marginalitas Jakarta dalam Novel Sisi Tergelap Surga Brian Khrisna - Muhammad Zanika Esa Putra; Latifah Winda Hamidah (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2026)
ABSTRACT   This study examines the struggle for survival among marginalized communities in Brian Khrisna’s novel Sisi Tergelap Surga through the lens of the sociology of literature. The research aims to reveal the forms of marginalization and the struggles of marginalized characters as reflections of urban social realities, particularly in Jakarta. This qualitative research employs a library research method, using the novel as the primary data source and theoretical books, academic journals, and social data as secondary sources. The analysis was conducted through close reading to identify patterns of marginalization and the characters’ strategies for survival within socio-economic urban contexts. The findings indicate that Brian Khrisna’s Sisi Tergelap Surga portrays three major forms of marginalization: social, economic, and gender-based. The characters face poverty, discrimination, and structural injustice but persist through solidarity, perseverance, and efforts to uphold their dignity. Jakarta is depicted as a symbol of modern paradox—where luxury coexists with deprivation, and progress contrasts with exclusion. Ultimately, Sisi Tergelap Surga not only depicts the suffering of marginalized individuals but also serves as a form of social critique and moral reflection on the deep-rooted inequalities that persist within contemporary society. Keywords: Marginilization; Social Reality; Social Inequality